Adoption determinants of the International Accounting Standards IAS/IFRS by the developing countries - Zehri, Fatma (2013)
This paper’s main objective is to identify certain explanatory factors that likely clarify the choice of applying IAS/IFRS adopted by developing countries (DCs) up until the year 2008. Based on a sample consisting of 74 DCs, the empirical results have indicated that the DCs most likely to adopt IAS/IFRS have a high level of economic growth, along with a legal system of common law and an advanced educational level. DOI: 10.1016/S2077-1886(13)70030-1